1976
DOI: 10.1021/bi00649a019
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of bacterial glycogen. 13. Purification and properties of the Escherichia coli B ADPglucose: 1,4-α-D-glucan 4-α-glucosyltransferase

Abstract: The Escherichia coli B glycogen synthase has been purified to apparent homogeneity with the use of a 4-aminobutyl-Sepharose column. Two fractions of the enzyme were obtained: glycogen synthase I with a specific activity of 380 mumol mg-1 and devoid of branching enzyme activity and glycogen synthase II having a specific activity of 505 mumol mg-1 and containing branching enzyme activity which was 0.1% of the activity observed for the glycogen synthase. Only one protein band was found in disc gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 51 publications
1
40
1
Order By: Relevance
“…Potassium fluoride and acetate have the reverse effect of being able to stimulate synthesis of protein-bound glycogen while not affecting glucose incorporation into added glycogen. The lack of effect of gluconolactone on the synthesis of acid-insoluble or soluble glycogen is to be contrasted with its total inhibition of ratliver [I71 and Escherichia coli glycogen synthases [18] and starch synthase [19].…”
Section: Distinction Between Mechanisms Of Incorporation Of [I4c]glucmentioning
confidence: 99%
“…Potassium fluoride and acetate have the reverse effect of being able to stimulate synthesis of protein-bound glycogen while not affecting glucose incorporation into added glycogen. The lack of effect of gluconolactone on the synthesis of acid-insoluble or soluble glycogen is to be contrasted with its total inhibition of ratliver [I71 and Escherichia coli glycogen synthases [18] and starch synthase [19].…”
Section: Distinction Between Mechanisms Of Incorporation Of [I4c]glucmentioning
confidence: 99%
“…Likewise, citrate was found to lower the K, of Escherichia coli glycogen synthase for glycogen 11-to 15-fold (8). Critical characterization of the E. coli enzyme showed that it contained large amounts of endogenous primer (4), thus possibly accounting for the unprimed synthesis. The unprimed reaction catalyzed by the E. coli glycogen synthase was found to be influenced by endogenous primer and citrate concentration as well as by glycogen-branching enzyme (8).…”
mentioning
confidence: 97%
“…is enzym fratio has been purified about 1,000fold frm maize kernels for the eosrmnuitant amykAw-exseder (ae). Previous reports have shown glycogen and starch synthase fractions from a number of sources catalyze a-glucan synthesis in the absence of added primer, when in the presence of high concentrations of citrate (4,6,8). This reaction has been termed "unprimed" starch and glycogen synthesis.…”
mentioning
confidence: 99%
“…The biosynthesis of glycogen requires three enzymes, ADPglucose pyrophosphorylase (EC 2.7.7.27), glycogen synthase (EC 2.4.1.21), and glycogen branching enzyme (EC 2.4.1.18), which are encoded by gigC, gigA, and gigB, respectively. The enzymes have been previously purified (9,20,27,28). The genes have been cloned on a single 10.5-kilobase (kb) genomic fragment (41), and their nucleotide sequences have been determined (4,5,35).…”
mentioning
confidence: 99%